HUBUNGAN LAMA PENGGUNAAN KONTRASEPSI HORMONAL (PIL) DENGAN HIPERTENSI DI DUSUN SIDO MUKTI KELURAHAN TANJUNG SELAMAT - Siti Saodah; Endam Apulina Br. Sembiring (Universitas Pahlawan Tuanku Tambusai, 2022)
Hormonal contraceptives contain estrogen and progesterone. Estrogen is a hormone that can increase electrolyte retention in the kidneys, resulting in an increase in sodium and water reabsorption which causes hypervolemia, then cardiac output increases and blood pressure increases. Women who have used hormonal contraceptive methods for a long time have a higher chance of suffering from hypertension compared to women who have not used hormonal contraceptive methods for a long time (Lestari, 2018). The purpose of this study was to determine the relationship between the use of hormonal contraceptive pills and the incidence of hypertension in the Sido Mukti Hamlet, Tanjung Selamat Village in 2021. The research method used is descriptive with a cross sectional approach. The sample is 36 respondents with total sampling technique. The statistical test used is the Chi Square Test. From the results of statistical tests, it was found that p value = 0.009 (α = 0.05), thus the p value was smaller than alpha so that Ho was rejected. So it can be concluded that there is a long relationship between the use of hormonal contraceptives (Pills) in Sido Mukti Hamlet, Tanjung Selamat Village. Keywords: duration of contraceptive use, hypertansion